2020
DOI: 10.1016/j.annonc.2020.03.299
|View full text |Cite
|
Sign up to set email alerts
|

JSCO—ESMO—ASCO—JSMO—TOS: international expert consensus recommendations for tumour-agnostic treatments in patients with solid tumours with microsatellite instability or NTRK fusions

Abstract: A Japan Society of Clinical Oncology (JSCO)-hosted expert meeting was held in Japan on 27 October 2019, which comprised experts from the JSCO, the Japanese Society of Medical Oncology (JSMO), the European Society for Medical Oncology (ESMO), the American Society of Clinical Oncology (ASCO), and the Taiwan Oncology Society (TOS). The purpose of the meeting was to focus on what we have learnt from both microsatellite instability (MSI)/ deficient mismatch repair (dMMR) biomarkers in predicting the efficacy of ant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
101
0
9

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 104 publications
(110 citation statements)
references
References 89 publications
0
101
0
9
Order By: Relevance
“…We have also demonstrated a link between YIF1B expression and TMB and MSI in some cancer types, and certain tumors also exhibit co-expression of YIF1B with the major MMR genes and methylation transferases. Previous studies have correlated TMB and MSI to patients' drug responses, especially for drugs that target immune checkpoint inhibitors, such as a TGF-β antagonist and PD-1 inhibitor [27][28][29][30][31][32]. We propose, therefore, that YIF1B could be deployed as an additional indicator for immune therapy evaluation of cancer patients after administration.…”
Section: Discussionmentioning
confidence: 98%
“…We have also demonstrated a link between YIF1B expression and TMB and MSI in some cancer types, and certain tumors also exhibit co-expression of YIF1B with the major MMR genes and methylation transferases. Previous studies have correlated TMB and MSI to patients' drug responses, especially for drugs that target immune checkpoint inhibitors, such as a TGF-β antagonist and PD-1 inhibitor [27][28][29][30][31][32]. We propose, therefore, that YIF1B could be deployed as an additional indicator for immune therapy evaluation of cancer patients after administration.…”
Section: Discussionmentioning
confidence: 98%
“…Considering MSI/dMMR as inclusion criterion for clinical trial enrollment, it is worthy to note that the frequency of MSI/dMMR misdiagnosis is not rare in real-life practice routine [28]. Therefore, attention should be devoted in MSI/dMMR diagnostic methods with potentially a systematic central review [29][30][31]. Two standard reference methods, namely immunohistochemistry (IHC) and polymerase chain reaction (PCR), are recommended for the detection of MSI/dMMR status.…”
Section: What Is the Best Way To Screen Patients For Msi/dmmr? Immunomentioning
confidence: 99%
“…Nonetheless, the diagnostic accuracy of NGS-based algorithms is not as certain as these of IHC and PCR. Moreover, the applicability of NGS approaches in a real-life routine has not been demonstrated, and they should only be carried out at selected specialist centres or through validated central laboratory methods [30].…”
Section: What Is the Best Way To Screen Patients For Msi/dmmr? Immunomentioning
confidence: 99%
See 1 more Smart Citation
“…Immunotherapy offers a promising avenue in management of many gastrointestinal malignancies specifically in treatment of gastroesophageal cancers and hepatocellular carcinoma [13]. In addition, ICIs can be used in patients with chemotherapy-resistant tumors through tissue agnostic approval for MSI-H and high mutational burden tumors [14]. ICIs have shown that they are not only efficacious but have superior safety profile as well [15].…”
Section: Introductionmentioning
confidence: 99%